Barcelona, Naples and Salonika: Ethnic and Civic Nationalism in Three Mediterranean Port Cities (1888–1915) - Daniele Conversi (Histories, 2023)
How far is port cities’ cosmopolitan inclination reflected in the type of nationalism prevailing in the surrounding area or region? How do these relationships change in different timeframes, one determined by nationalist modernization, the other by neoliberal globalization? This article attempts to respond to this question by looking at three Northern Mediterranean port cities (Barcelona, Naples, and Salonica) in two different time settings: the advent of the centralizing nation-state preceding WW1 and the advent of free-market deregulation policies adopted worldwide since the 1980s. It does so by adapting a new critical reading of Hans Kohn’s dichotomy on civic/ethnic nationalism—and extending it to the realm of culture in an age of deep global transformations.